2021
DOI: 10.1109/access.2021.3104527
|View full text |Cite
|
Sign up to set email alerts
|

A Multicriteria Decision Making Taxonomy of IOT Security Challenging Factors

Abstract: Internet of things (IoT) is leading a new digital age. IoT is regarded as the significant frontier that can improve almost all aspect of our lives. Currently, the IoT technology faces several challenges to academic researchers and industry practitioners, mainly that related with security of data. The objective of this study is to develop a prioritization-based taxonomy of the challenging factors that could hinders the security of IoT. By conducting the literature review and questionnaire survey studies 21 chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Reference [10] conducted a survey and literature review that identified 21 security factors mapped in four domains (i.e., smart cities, homes, wearables, and health care). They used the fuzzy-AHP method, rather than cryptographic algorithms, to rank the factors in order of their importance to IoT technology security.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [10] conducted a survey and literature review that identified 21 security factors mapped in four domains (i.e., smart cities, homes, wearables, and health care). They used the fuzzy-AHP method, rather than cryptographic algorithms, to rank the factors in order of their importance to IoT technology security.…”
Section: Related Researchmentioning
confidence: 99%
“…Some studies reviewed a particular application perspective, like smart homes, cities, or healthcare [5], [11]. Certain studies focused on IoT QA [3], [6], [8], while many others performed generic surveys on the factors influencing IoT security [3], [7], [10], [12], [13], [15]. Therefore, as far as we know, this study is the first to compare and discuss the existing metrics that quantify IoT parameters.…”
Section: Related Researchmentioning
confidence: 99%
“…[33][34][35][36] Numerous decision-making techniques exist. [37][38][39][40][41][42] Thus, we applied the FAHP technique as it is an effective way to handle the MCDM. Considering the successfulness of FAHP in other engineering domains, we also consider it to prioritize the identified security risks against each phase of SDLC.…”
Section: Background and Motivationmentioning
confidence: 99%
“…As a result, determining the significance and priority of numerous security risks and categories may be referred to as the multicriterion decision-making (MCDM) dilemma [33][34][35][36]. Numerous decision-making techniques exist [37][38][39][40][41][42]. Thus, we applied the fuzzy AHP technique as it is an effective way to handle the MCDM.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The search keywords are linked using OR and, AND operators. We used the following search string for this study as reported in other studies [20][21]. ("Contact tracing app" OR "digital contact tracing" OR "close contacts" OR "exposure notification" OR "digital contacts" OR "blockchain-based contact tracing" OR "blockchain-based digital contacts") AND ("security and privacy" OR "trust" OR "legal use") AND ("Benefits" OR "Success" OR "Advantages").…”
Section: 1 Study Selection Criteriamentioning
confidence: 99%